Antiamoebic activity of extracted alkaloids of Capparis spinosa in Laboratory mice - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
The current study was concerned with the effect of alkaloid extract of the aerial parts of Capparis spinosa against Entamoeba histolytica and compared with drug Metronidazole in the laboratory mice .Stool samples were collected from people infected with maebiasis to infect laboratory mice . The alkaloid compounds were separated by thin chromatography technique (TLC) and identified by spectral methods represented by spectral infrared (IR) and altraviolate (UV) . the stady include determining mid-term lethal dose LD50 of the extract as the concentration was 21.65 g / kg . The effect dose of the extract was tested on the infected experimental mice with Entamoeba histolytica after 10 days of the infection compared with the mice infected and treated with the drug Metronidazole and with the control mice in which the therapeutic dose used was 2.89 g / kg for seven days.